The integration of imagery training to increase gymnastic skill learning outcomes - Aqim Visalim; Sri Winarni; Tri Ani Hastuti (Journal of Education and Learning (EduLearn), 2019)
Imagery training had been proven to improve skills in some athletes in sports training. Yet in education, it left a big question. The purpose of this research was to prove whether the learning process integrated by imagery training could improve learning outcomes in cartwheel skill. The research method used Classroom Action Research method with two cycles. Each cycle consisted of four stages, namely: preparation, implementation, observation, and reflection. The action was conducted by the integration of imagery training in learning cartwheel motion. Data collection techniques used observation and performance test. The increase of learning outcomes in skill aspects of 34 students reached 58.82% in the first cycle, and increased to be 76.67% in the second cycle. The result of the study showed that through learning process integrated by imagery training could improve learning outcomes in gymnastic material about cartwheel skill.